Methodology in sports history - Vamplew, Wray; Day, Dave (Sport in the global society. Historical perspectives, 2018)
The process of converting the 'past' into 'history' involves engagement with a multitude of different sources and methods, and sports historians inevitably participate in the same debates over approaches and methodologies as their counterparts in other historical disciplines. This book deals with some of these innovations. It is divided into two sections, the first offering chapter-length studies of particular methodologies, and the second, brief responses from experts in their fields to the question 'what can sports historians learn from other disciplines?.